VARIAN HAMZAH DAN ALIF PADA SURAH AL-KAHFI (TINJAUAN EJAAN BAHASA ARAB) (Lisanul Arab: Journal of Arabic Learning and Teaching, 2023)
In the writing of the Usmani Rasm Mushaf, the rules of alif and hamzah have the form and uniqueness of writing. This study describes the forms and analyzes the causes of the variants of writing hamzah and alif in Surah Al-Kahf. The purpose of this study is to provide education about the uniqueness and variants of writing hamzah and alif in the Holly Qur'an. This research is a qualitative descriptive research with library research research design. The data of this research are hamzah and alif which are sourced from the Surah Al Kahf in the Mushaf Pojok Kudus. Data collection techniques used the documentation method with research instruments in the form of data cards and recapitulation sheets. The data analysis technique uses an interactive analysis model with data reduction; data display; and drawing conclusions. The results of this study contained 190 Hamzah data and 235 Alif data contained in Surah Al Kahfi Mushaf Pojok Kudus. From 193 hamzah data, 36 data are hamzah qathi' category at the beginning of isim, 30 data are hamzah qathi' category at the beginning of fi'il, 62 data are hamzah washl category at isim, 18 data are hamzah washl category at fi'il, 21 the data is the hamzah category in the middle of the word, 12 data is the hamzah category at the end of the word, and 11 data is the hamzah category in the harf. Then there are 235 alif data consisting of 67 alif mamdudah data in the middle of the word, 156 alif mamdudah data at the end of the word, and 14 alif maqshurah data. The variants of writing hamzah and alif in the Surah Al Kahfi Mushaf Pojok Kudus are caused by the category of words that compose them and the use of the Ottoman rule which maintains the authenticity of the writing because of I'jazi.